(3GdHgLI aj TQM GdJMaIs - (3Ydj Hf YHO GdSdGe Hf Ydj, CHh GdMSf GdoqJoShdj, J (B1258(3g`s; (3CHh HcQ eMeO Hf eMeO Hf YGUe GdeGdcj GdbjSjs ((3eMeO Hf SjO GdeNJGQ s)
(3ChdgG (B:s
(3GdMeO ddg GdhGMO GdCMO , Pi GdLdGd hGdEcQGe hHYO ajbhd deG cGfJ JMaI GdMcGe ef CLd eG Cda ai Yde GdhKGFb hGdEHQGe GdSdGeI fXegG hef Gddg YdjfG HJOQjSgG hEbQGFgG WdH efi GdcKjQ ef WdHI GdhbJ Cf CVY dge TQMkG s
(3BNQgG (B:s
(3bdJ (B: (3hgh XGgQ , aEf CKHJJ GdhUjaI hef eYgG VQQge HTgGOI ef Scf eYge RLQ GdXGde HGdSLf hGdVQH , hdG JYRd hGMOI efgf Yf GdCgd , dCf ZGdH GdfSGA ai gPG GdReGf djJhUdf ddecQhg hGdaSGO GfJgi s
(3HgG agQSJ ddCHhGH haUhd GdLRAs
(3HgG fXGe GdJYbjHIs
(3fSNI eUMMIs
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI SjFI s
(3GdfSNI HgG JdhjK , CQVg s
Keywords: (3Gdabg GdESdGejs